The Urgency of Reformulating The Narcotics Law in Response to The Digital Modus Operandi of Drug Trafficking Syndicates Using The Zangi App - Abdurrafi Hibatullah; Kayus Kayowuan Lewoleba (Jurnal Daulat Hukum, 2026)
The development of information technology has driven a transformation in the modus operandi of illicit drug trafficking from conventional methods to digital methods through encrypted communication applications, such as Zangi, which complicates the tracking and evidence gathering processes for law enforcement agencies. This study aims to analyze the modus operandi of narcotics trafficking syndicates through digital media and to examine the urgency of reformulating Law No. 35 of 2009 on Narcotics. This study is a normative legal research employing legislative, conceptual, and case based approaches. The findings indicate that current regulations do not explicitly address drug trafficking based on electronic systems, rendering them ill suited to the evolution of digital technology. Although electronic evidence is recognized under criminal procedure law, its implementation still faces technical challenges and limitations in law enforcement capacity. Therefore, a reformulation of the Narcotics Law is necessary, encompassing the expansion of the legal definition of digital based criminal offenses, the strengthening of cyber oversight authorities, and the regulation of electronic platform liability to achieve an adaptive and effective criminal law policy in the digital era.